A genetic system for direct selection of gene-positive clones during recombinational cloning in yeast - Noskov, Vladimir (Oxford University Press, 2002)
Transformation-associated recombination (TAR) is a cloning technique that allows specific chromosomal regions or genes to be isolated directly from genomic DNA without prior construction of a genomic library. This technique involves homologous recombination during spheroplast transformation between genomic DNA and a TAR vector that has 5′ and 3′ gene targeting sequences (hooks). Typically, TAR cloning produces positive YAC recombinants at a frequency of ∼0.5%; the positive clones are identified by PCR or colony hybridization. This paper describes a novel TAR cloning procedure that selects positive clones by positive and negative genetic selection. This system utilizes a TAR vector with two targeting hooks, HIS3 as a positive selectable marker, URA3 as a negative selectable marker and a gene-specific sequence called a loop sequence. The loop sequence lies distal to a targeting hook sequence in the chromosomal target, but proximal to the targeting hook and URA3 in the TAR vector. When this vector recombines with chromosomal DNA at the gene-specific targeting hook, the recombinant YAC product carries two copies of the loop sequence, therefore, the URA3 negative selectable marker becomes mitotically unstable and is lost at high frequency by direct repeat recombination involving the loop sequence. Positive clones are identified by selecting against URA3. This method produces positive YAC recombinants at a frequency of ∼40%. This novel TAR cloning method provides a powerful tool for structural and functional analysis of complex genomes.